Editorial - Rowlett, Peter; Jones, Matthew M. (MSOR Connections, 2020)
This special issue of MSOR Connections is based on contributions to a workshop, ‘Programming in the undergraduate mathematics curriculum’, which took place at Middlesex University on 27th June 2019, and other submissions received on the same theme.